Efektivitas Pelaksanaan Program TNI Manunggal Membangun Desa di Kecamatan Pemulutan Barat Kabupaten Ogan Ilir - Zamroni, Zamroni; Prihatini, Lishapsari; Mardianto, Mardianto (@-Publik: Jurnal Administrasi Publik, 2022)
Since the 1980s, Indonesian Army has implemented programs solely to help overcome the difficulties of rural communities, the program which was originally known as ABRI Masuk Desa (AMD) has now changed to TNI Manunggal membangun Desa (TMMD). The 108th TMMD program of Kodim 0402/OKI in Pemulutan Barat sub-district, OganIlir district in collaboration with the local government as a budget provider for infrastructure development will run well and effectively if it is carried out through careful planning and preparation stages and serious implementation. The dimensions of target accuracy for the short and long term, program socialization through communication and delivery of information, program objectives with indicators of implementing activities and achieving goals, as well as dimensions of program effectiveness with indicators of quality and quantity of activity results and the time used, become benchmarks for the effectiveness of program implementation 108th TMMD 2020.